Student Rationality in School Selection: Navigating Values, Cost, and Distance in Urban Makassar - Saputra, Ilham; Ahmad, M. Ridwan Said; Zulqarnain, A Muhammad Iman (Citra Media Publishing, 2025)
School choice is often assumed to be a rational decision aligned with spatial efficiency, as reflected in education zoning policies. However, in the context of urban peripheries, such decisions are frequently shaped by more complex social, cultural, and economic factors. This study aims to examine the rationality behind students' choice of SMP Hasyim Asyari, located in Tallo District, Makassar City—a non-favorite school with limited facilities and an unstrategic location. Employing a descriptive qualitative approach and case study method, data were collected through in-depth interviews with several students and one teacher, as well as direct observation of the school environment. The findings reveal that students’ decisions were based on religious values, social comfort, affordability, and recommendations from social networks, rather than prestige or geographical proximity alone. These practices reflect community agency in resisting the symbolic dominance of the formal education system through subtle yet significant forms of everyday resistance. The study recommends the need for educational policies that are more context-sensitive and responsive to the values of local communities.